Case report: Expanding the understanding of the adult polyglucosan body disease continuum: novel presentations, diagnostic pitfalls, and clinical pearls - Gayed, Matthew M.; Sgobbi, Paulo; Pinto, Wladimir Bocca Viera De Rezende; Kishnani, Priya S.; Koch, Rebecca L. (Frontiers in Genetics, 2023)
Introduction: Adult polyglucosan body disease (APBD) is the adult-onset form of glycogen storage disease type IV (GSD IV) caused by biallelic pathogenic variants in GBE1. Advances in the understanding of APBD natural history published in recent years has led to the use of discrete descriptors ("typical" versus "atypical") based on adherence to traditional symptomatology and homozygosity for the p.Y329S variant. Though these general descriptors are helpful in summarizing common findings and symptoms in APBD, they are inherently limited and may affect disease recognition in diverse populations. Methods: This case series includes 3 American patients (Cases 1-3) and 4 Brazilian patients (Cases 4-7) diagnosed with APBD. Patient reported outcome measures (PRO) were employed to evaluate pain, fatigue, and quality of life in Cases 1-3. Results: We describe the clinical course and diagnostic odyssey of 7 cases of APBD that challenge the utility and efficacy of discrete descriptors. Cases 1-3 are compound heterozygotes who harbor the previously identified deep intronic variant in GBE1 and presented with "typical" APBD phenotypically despite lacking two copies of the pathogenic p.Y329S variant. Patient reported outcome measures revealed moderate levels of pain and fatigue as well as impacted quality of life. Cases 4-7 have unique genotypic profiles and emphasize the growing recognition of presentations of APBD in diverse populations with broad neurological manifestations. Conclusions: Collectively, these cases underscore APBD as a spectrum disorder existing on the GSD IV phenotypic continuum. We draw attention to the pitfalls of commonly used genetic testing methods when diagnosing APBD and highlight the utility of patient reported outcome questionnaires in managing this disease.